The Effectiveness of the Elsa Speak Application in Enhancing Speaking Skills among Students at University - Yanpitherszon Liunokas (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study investigates the effectiveness of the Elsa Speak application in enhancing speaking skills among students at Universitas Nusa Cendana, Kupang. As English language proficiency becomes increasingly crucial in academic and professional contexts, innovative technological solutions like Elsa Speak—an AI-powered pronunciation and speaking coach—offer promising alternatives to traditional speaking instruction. The research examines how students at the Fourth Semester Students of English Education Department, Nusa Cendana University, Kupang, NTT utilize the application's speech recognition technology, personalized feedback mechanisms, and interactive exercises to improve their pronunciation, fluency, and overall speaking confidence. Employing a mixed-methods approach, the study collected data from English language learners through pre-tests and post-tests, questionnaires, and interviews to assess learning outcomes and user experiences. Findings indicate that regular use of Elsa Speak resulted in measurable improvements in pronunciation accuracy and speaking fluency, with students reporting increased confidence in oral communication. However, challenges such as limited internet connectivity and the need for self-discipline in independent learning were identified as potential barriers. The study concludes that while Elsa Speak serves as a valuable supplementary tool for speaking practice, its effectiveness is maximized when integrated with instructor-led activities and peer interaction. These findings contribute to the growing body of research on mobile-assisted language learning (MALL) and provide practical insights for educators in Indonesian higher education contexts seeking to incorporate technology-enhanced language instruction.